Non-invasive computed tomography coronary angiography as a gatekeeper for invasive coronary angiography - de Graaf, Fleur R. (Springer Netherlands, 2012)
To determine the rate of subsequent invasive coronary angiography (ICA) and revascularization in relation to computed tomography coronary angiography (CTA) results. In addition, independent determinants of subsequent ICA and revascularization were evaluated. CTA studies were performed using a 64-row (n = 413) or 320-row (n = 224) multidetector scanner. The presence and severity of CAD were determined on CTA. Following CTA, patients were followed up for 1 year for the occurrence of ICA and revascularization. A total of 637 patients (296 male, 56 ± 12 years) were enrolled and 578 CTA investigations were available for analysis. In patients with significant CAD on CTA, subsequent ICA rate was 76  %. Among patients with non-significant CAD on CTA, subsequent ICA rate was 20 % and among patients with normal CTA results, subsequent ICA rate was 5.7 % (p < 0.001). Of patients with significant CAD on CTA, revascularization rate was 47 %, as compared to a revascularization rate of 0.6 % in patients with non-significant CAD on CTA and no revascularizations in patients with a normal CTA results (p < 0.001). Significant CAD on CTA and significant three-vessel or left main disease on CTA were identified as the strongest independent predictors of ICA and revascularization. CTA results are strong and independent determinants of subsequent ICA and revascularization. Consequently, CTA has the potential to serve as a gatekeeper for ICA to identify patients who are most likely to benefit from revascularization and exclude patients who can safely avoid ICA.